A new chemical approach for preventing the anti-social use of ammonium nitrate - Gezerman, Ahmet Ozan (European Journal of Chemistry, 2017)
The aim of the present study is to limit the detonation properties of ammonimum nitrate fertilizers used in agriculture. The results presented in this paper are obtained by using analytical methods. This study also evaluated the physiochemical properties of nitrogenous fertilizers such as the specific heat, explosive enthalpy, and the effects of dolomite and fly ash additives that have been suggested for increasing the nutritional content of ammonium nitrate fertilizers. The results obtained regarding additives differ from those of previous studies. The present study produced important results regarding additives, and efforts were made to limit certain physical properties such as the detonation enthalpy and detonation velocity.